The effect of âpatikan keboâ(Euphorbia hirta L) preparations on erythrocyte number, haemoglobin level and haematocrit value of chicken infected with Eimeria tenella - Wardhana, April H; Kencanawati, E; ., Nurmawati; ., Rahmaweni; Jatmiko, C.B (Indonesian Journal of Animal and Veterinary Sciences, 2001)
Patikan keboâ (Euphorbia hirta L) is a medicinal plant mostly used to treat gastro-intestinal track problems empirically. The aim of this study was to determine the effect of distillation, infusion and extract of âpatikan keboâ (Euphorbia hirta L) preparations on erythrocyte number, haemoglobin level and haematocrit value in chickens that were infected by Eimeria tenella. Twenty four Hubbard strain broiler chicken raised from one-day-old until three-week-old were used for this study and divided randomly into 4 groups: P 0 (control), P I (distillation treatment), P II (infusion treatment), and P III (extract treatment). A total of 5.000 oocyst of E. tenella were infected into each chicken and the dose of Euphorbia hirta L was 500 mg/kg Wb. A completely randomized design was used and the data were tested by ANOVA. The result indicated that distillation, infusion and extract preparations of Euphorbia hirta L had the potency to increase erythrocyte number, haemoglobin level and haematocrit value. Â  Key word : Eimeria tenella, Euphorbia hirta L, erythrocyte, haemaoglobin, haematocrit